2022
DOI: 10.3390/ma15124357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling Rate on Mechanical Properties, Translucency, Opalescence, and Light Transmission Properties of Monolithic 4Y-TZP during Glazing

Abstract: A standard cooling rate has not been established for glazing; therefore, the effects of the cooling rate on the properties of zirconia need to be evaluated to predict outcomes in clinical practice. 4Y-TZP glazed at three different cooling rates was analyzed to estimate the effect of cooling rate during glazing on the mechanical and optical properties. Hardness tests, field-emission scanning electron microscopy analysis, X-ray diffraction analysis, flexural strength measurement, and optical property evaluations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In yttria-stabilized zirconia (YSZ), the TP exhibited an exponential decrease as the thickness increased [ 12 , 38 ]. For A2 shade zirconia (4Y), the TP value was reported to exponentially decrease from 12.54 to 5.4 as the thickness increased from 1 mm to 2 mm [ 39 ]. The TP values of natural human dentin are approximately 7 and 21 for the incisors and molars, respectively, at a thickness of 2 mm [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In yttria-stabilized zirconia (YSZ), the TP exhibited an exponential decrease as the thickness increased [ 12 , 38 ]. For A2 shade zirconia (4Y), the TP value was reported to exponentially decrease from 12.54 to 5.4 as the thickness increased from 1 mm to 2 mm [ 39 ]. The TP values of natural human dentin are approximately 7 and 21 for the incisors and molars, respectively, at a thickness of 2 mm [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in Δb* contributed to a significant increase in the OP from the EL to DL. In YSZ, the OP value increases with increasing thickness [ 12 , 39 , 42 ]. In colored zirconia, the increase in the OP value with increasing thickness was greater than that in uncolored zirconia [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeong (2022) concluded that a higher cooling rate did not result in a significant difference in grain size, flexural strength, average transmittance, and translucency, although it did lead to a slight reduction in hardness. The influence of cooling rate during the glazing process on the mechanical and optical properties of 4Y-TZP seems to be minimal and of little clinical significance [69].…”
Section: Regular or Speed Sinteringmentioning
confidence: 97%
“…Secondly, the optical properties of CAD-CAM materials may undergo changes during prosthesis repair or adjustments such as grinding or polishing [ 20 22 ]. Meanwhile, wear, aging, and acid etching occur naturally to the restoration [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%